Prognostic value of right ventricular systolic function in cardiac amyloidosis. (2nd July 2016) - Bodez, Diane; Ternacle, Julien; Guellich, Aziz; Galat, Arnault; Lim, Pascal; Radu, Costin; Guendouz, Soulef; Bergoend, Eric; Couetil, Jean-Paul; Hittinger, Luc; Dubois-Randé, Jean-Luc; Plante-Bordeneuve, Violaine; et al.
Abstract: Background : Right ventricular (RV) dysfunction is a strong predictor of poor outcomes in heart failure. Its prognostic meaning in cardiac amyloidosis (CA) is under-investigated. Methods : Hundred and twenty nine patients with suspected CA and an interventricular septum thickness (IVST) ≥ 12 mm underwent echocardiography with measurement of left ventricular (LV) and RV longitudinal strain (LS), late gadolinium-enhancement (LGE) cardiac MRI, and standard evaluation. Results : Among 82 confirmed CA, types were immunoglobulin light chain (AL, n  = 26), hereditary transthyretin (m-TTR, n  = 37) and senile (WT-TTR, n  = 19). Compared to those without, CA patients had significantly lower RV fractional shortening (RV-FS), tricuspid annular plane systolic excursion (TAPSE), tissue Doppler systolic velocity, and global RV-LS, without any difference among the CA types. RV-LGE, observed in 62% of CA patients, was associated with lower global and basal RV-FS. Median follow-up was 8(2; 16) months. Using multivariate analysis, NYHA-class and low TAPSE independently predicted major adverse cardiac event (MACE) defined as death, heart transplantation and acute heart failure. Independent determinants of TAPSE < 14 mm, the best cut-off value, were LV ejection fraction (LVEF), estimated filling pressure (E/E′), NT-proBNP and pulmonary artery pressure, but not RV-LGE. Conclusions : RV dysfunction is common in CA. Its routine evaluation by a simple TAPSE may be an aid in assessing the prognosis of CA patients.